2017
DOI: 10.1515/acph-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Testing of resveratrol microemulsion photostability and protective effect against UV induced oxidative stress

Abstract: Testing of resveratrol microemulsion photostability and protective effect against UV induced oxidative stressResveratrol is well known for its antioxidant activity and susceptibility to ultraviolet radiation. Development of formulations providing improved stability and relevant drug delivery of resveratrol is still a challenging task. The aim of this study was to determine protective characteristics of formulated microemulsions by evaluating photoisomerization of resveratrol and to investigate the effects of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…↑Cell viability ↓Apoptosis ↑Activation of SIRT1 [87] Cells first treated with 2% of resveratrol for 2 hr, followed by UVB irradiation (5-100 mJ/cm 2 ) ↑Cell viability ND [88] Cells treated with 5-25 μM resveratrol for 24 hr, followed by irradiation with UVB (40 mJ/cm 2 )…”
Section: Anti-uv Irradiationmentioning
confidence: 99%
“…↑Cell viability ↓Apoptosis ↑Activation of SIRT1 [87] Cells first treated with 2% of resveratrol for 2 hr, followed by UVB irradiation (5-100 mJ/cm 2 ) ↑Cell viability ND [88] Cells treated with 5-25 μM resveratrol for 24 hr, followed by irradiation with UVB (40 mJ/cm 2 )…”
Section: Anti-uv Irradiationmentioning
confidence: 99%
“…Resveratrol is also reported to promote metabolism and reduce oxidative stress, which can also be used as an antioxidant affecting the synthesis of nitric oxide that regulates DNA damage, cell cycle, apoptosis, and proliferation [14]. In addition, a number of studies on resveratrol have revealed possible mechanisms of UV protection, such as inhibiting the activation of NF-κB and preventing the expression of MMP-9 [15,16]. Resveratrol has gradually been found to have potential health benefits, including antiaging, anti-diabetes, anti-cancer, and anti-dementia [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…MEs have a high capacity for drug loading, and because they have a high capacity for solubilizing drugs [62], they can get through the stratum corneum barrier and partition the medication into the skin [63,64]. A study indicated that MEs protect the RSV from ultraviolet B (UVB) radiation for up to 1 h and delay photodegradation which further helps in uptakes of RSV in the skin [65].…”
Section: Microemulsionsmentioning
confidence: 99%